Molecular dynamics simulations of metal–organic framework membranes for seawater desalination - Hong, Terence Zhi Xiang (Nanyang Technological University, 2023)
Access to clean water is essential for sustaining life on Earth, which drives a need to develop new technologies to purify water. Furthermore, since 97% of the water originates from the sea, there are high prospects for extracting purified water from seawater. Therefore, seawater desalination plays a significant role in meeting water consumption demands. Among the three types of commercially available seawater desalination technologies, i.e., membrane separation, chemical separation, and thermal driven, membrane separation is the most preferred due to its simple design and energy efficiency. In reverse osmosis (RO), the semi-permeable membrane is used to separate salt ions from the water molecules by allowing the latter to pass through the membrane into the permeate side while retaining the salt ions at the feed side. Furthermore, conventional RO membranes made from polymers have to balance the ion separation and membrane flux while experiencing high membrane swelling and poor mechanical and chemical stability. Although progress has been made towards addressing the above problems, serious challenges such as power consumption and concentration polarization are yet to be resolved to develop more efficient and cost-effective membranes. Due to the high salt concentration in seawater, a post-treatment process is needed to further reduce the salt concentration in the treated water. Therefore, capacitive deionization (CDI) is employed as a low energy process to improve water quality. Metal–organic frameworks (MOFs) is a compound-based material consisting of metal nodes connected by organic linkers or ligands. This novel material have gained interest in membrane and electrode design for seawater desalination because of their naturally high porosity, good material compatibility with polymers, and the ability to enhance the porosity of composite membranes and electrodes. Furthermore, the potential to modify the metal nodes and the organic linkers in MOFs through functionalization provides a diverse range of morphology and chemical properties. An efficient method of modifying MOFs without significantly altering their morphologies is to use different types of metal nodes with varying concentrations. Additionally, there is a lack of studies into the performance issues of MOFs caused by water-induced defects. Computational studies are utilized to reduce the time and resources needed to screen novel MOF materials and provide an in-depth understanding of them on the nanoscale. Therefore, this study focused on investigating the effects of metal nodes, water-induced defects, MOF morphology, and bimetallic MOFs on the water flux and salt rejection in RO and CDI seawater desalination via molecular dynamics (MD) simulation. The effect of atom-based metal nodes in Zeolitic imidazolate frameworks (ZIFs) on CDI desalination to simultaneously remove both salty and Cr(VI) ions is studied. The simulation results show that ion adsorption in the ZIF electrode surface(s) occurs at its metal and nitrogen atoms, and ion rejection can be as high as 99.3% for salty ions. However, the heavy metal ions Cr6+ and Cl– agglomerate constantly and the ion adsorption by the ZIFs deteriorates with time. It is also found that water flux is affected by the number of salt ions both at the entrance and in the middle of the nanochannel and ZIF hydrophilicity, which is influenced by the type of metal atoms used. Among the four ZIFs tested, CdIF-1 performs best. Water-based substitutional defects in ZIF-8 membranes can affect their reverse osmosis (RO) desalination performance. These substitutional defects can either be Zn defects or linker defects. The results show that ion adsorption on the membranes occurs at the zinc nodes, nitrogen atoms or the defect sites. Complete NaCl rejection can be achieved by introducing defects to change the size of the pores, while the presence of linker defects increases the hydrophilicity of the membranes. Overall, water-based substitutional defects in a ZIF-8 structure reduce the water flux and influence the hydrophilicity and ion adsorption performance of the ZIF-8 RO membrane. Of the seven ZIF-8 structures tested, pristine ZIF-8 exhibits the best RO desalination performance. Although the CuBDC and IRMOF-1 MOFs as two-dimensional (2D) membranes possess the same 1,4-benzenedicarboxylate linkers, they have different metal nodes which correspond to different molecular structures. The results indicate that the pore entrance of both MOF membranes exhibits a higher affinity towards Cl– ions than Na+ ions. Furthermore, complete ion rejection is achieved for both MOF membranes at half the thickness of their physical counterparts (CuBDC: ~50 Å and IRMOF-1: 40 Å). The lower water flux in the CuBDC membrane is also determined to be caused by the low water density inside the membrane. Of the two 2D MOF membranes tested, the IRMOF-1 membrane displays a higher water flux due to its more porous structure. Bimetallic Hexaaminobenzene (HAB)-derived 2D MOF RO membranes with different Co:Cu node ratios can influence the pore diameter, hydrophilicity, and ion affinity. A higher Co:Cu ratio will improve the hydrophilicity of the membranes and Cl– ion adsorption, while a smaller Co:Cu ratio will increase the pore diameter of the membrane. Therefore, the results reveal that a bimetallic MOF membrane with a Co:Cu ratio of 1:2 will provide optimal hydrophilicity and pore size to achieve the highest water flux out of the four membranes studied. Therefore, the study indicates that bimetallic MOF membranes have an advantage over monometallic MOF membranes by allowing the former to benefit from having two types of metal nodes. This Ph.D. study has investigated the effects of water-induced defects and metal node modification in MOFs for RO and CDI seawater desalination applications. The findings from this study are helpful in understanding the mechanisms of water transport and ion separation through these porous materials.